Creating value from mergers and acquisitions : - Sudarsanam, P. S. (Financial Times Prentice Hall, 2003)
Creating Value from Mergers and Acquisitions gives an integrated and international perspective. It develops an international and multidisciplinary perspective of M A, and considers M A as a process and not a mere transaction